THE DIFFERENCES OF THE DURATION OF FAMILY PLANNING PROGRAM REPORT BETWEEN USING GOOGLE SHEETS MEDIA AND MANUAL COUNTING METHOD AT PUSKESMAS SONGGON, SONGGON DISTRICT, BANYUWANGI REGENCY - Erlangga, Wildan Anugrah; Septiana, Fitri Nurina; Arrianti, Emilia Eka; Qualisa, Prafidina; Hakim, Lukman; Meitavany, Estya Nadya; A'yunin, Ulinnuha Qurrota; Lamara, Ariikah Dyah; Fatimah, Niswah Silmi; Adi, Pandu Satriya; Dewanti, Linda (Universitas Airlangga, 2020)
Based on the results of interviews with the coordinator of the family planning program at the Puskesmas Songgon, their data collection system was still written manually in the Kohort book which must then be classified and processed further to obtain processed data that describes the situation and conditions of the family planning program application in Songgon District. The aims of this research to determine the effectiveness and efficiency of the family planning program report duration between the use of Google Sheets media and the manual counting method at the Puskesmas Songgon. The implementation of the program were 23 May 2019 at Puskesmas Songgon Hall. This program was designed based on the needs of the field of family planning management at the Puskesmas Songgon. This program was created using a computer, the Google Sheets application, which is an application that resembles Microsoft Excel, but is managed by Google and accessed via a browser. It creates two types of formats, namely forms for data entry and automatic calculation reports. The results of this study, it can be seen that the program used by group 2 is 10 times more efficient in calculating the achievements of the family planning program.